(untitled) (Veterinary Science, 2019)
Campero chicken represents a productive alternative within the framework of semi-intensive poultry systems that seek to preserve animal welfare. The production protocol establishes restrictions linked to management strategies, among which is the maximum stocking density of birds allowed per unit area. The aim of this work was to evaluate the effect of the stocking density on the dynamic growth pattern, the uniformity by precision of body weight, the body conformation and the slaughter traits in male chickens of the experimental three way cross Campero Casilda. Birds were bred as a single group, in confinement, until 35 days, when they were randomly distributed in three treatments: Low Density: 6 birds / m2 (21 kg / m2), Recommended Density: 7 birds / m2 (24.5 kg / m2) and High Density: 8 birds / m2 (28 kg / m2) and access to the park was enabled until slaughter at 84 days. Within the limits tested in this work, neither the decrease in the density indicated by the protocol of production of Campero chickens, in search of greater welfare, nor its increase, in search of greater profitability, significantly affect body growth evaluated from the dynamic pattern of body weight and the record of conformation indicators based on linear measurements. Neither body weight uniformity nor the proportion of valuable cuts of butcher interest, abdominal fat content and carcass yield at slaughter, of Campero Casilda males, were affected. The evidence shows that the increase of stocking density does not produce detrimental effects on those traits of greater economic importance, in particular, body weight and traits at slaughter, for what a modification in this sense could be introduced in the protocol tending to favor the economic return in productive enterprises